KEBIJAKAN PROGRAM SEKOLAH GRATIS (PSG) DAN DAMPAKNYA TERHADAP AKSES LAYANAN MEMPEROLEH PENDIDIKAN DI PROVINSI SUMATERA SELATAN - Marzuki, Ervan (Publikasi Penelitian Terapan dan Kebijakan, 2011)
The government has made an effort to expand the access and the even distribution of the education and kept increasing the participation of the education and decreasing the discrepancy of the education level among the societies. The government of the Province of South Sumatera is the first province in Indonesia which has been performing the policy of the Free School Program. The aim of the Free School Program is for all school from Elementary School/ Islamic Elementary School till Senior High School weather state or private schools. The evaluation for the implementation of the policy needs doing to know the effectively of the policy. This research was done to analyze the retrospective policy which has orientation for the policy application (application oriented analysis) which has existed. They type of the research is the evaluation of the existed policy to arrange or complete the policy in the future. The research used the quantitative approachability which was done at the level of institution or community. The result of the research has shown that the program of the free school in South Sumatera Province which was begun at the year of 2009 has been able to increase the expansion of the access to get the education service. It was shown by the increasing of APK and APM and decreasing of DO numbers. Nevertheless, the monitoring and evaluating for the implementation of this program needs doing to guarantee the effectively of the activity.